Comparison of Mortality Rate Between Bipolar Hemiarthroplasty and Proximal Femoral Nail Anti-rotation for Intertrochanteric Fractures in Sanglah Hospital, Bali - Dusak, I Wayan Suryanto; Aryana, I Gusti Ngurah Wien; Dharmayuda, Cokorda Gde Oka; Subawa, I Wayan; Nugraha, Hans Kristian; Susila, Made Arya; Mahadhana, Sri (The Hip and Knee Journal, 2020)
Introduction: Intertrochanteric fractures occur in about 50% of all hip fracture events, with a mortality rate within 1 year after fracture reaching 15 to 20%. The most common treatment nowadays is either the bipolar hemiarthroplasty procedure or proximal femoral nail anti-rotation (PFNA), although there is still no consensus regarding which is better from the two, especially on patient mortality.Method: This study was an observational study using a retrospective cohort design. A total of 102 study subjects who met the inclusion requirements were grouped into 2 groups, one with bipolar hemiarthroplasty fixation treatment and another with PFNA fixation treatment. Mortality rate was recorded by survey 2 years after surgery.Results: Chi-square test showed that 2-year mortality rate after intertrochanteric fracture treated with bipolar hemiarthroplasty (21.4%) was significantly higher than the PFNA group (10.3%) (p = 0.028). Bipolar hemiarthroplasty group also had longer length of stay (50%) than the PFNA group (32.4%), albeit statistically insignificant (p = 0.13). There was no significant difference between the 2-year mortality rate and length of stay (p = 0.976).Conclusion: Patients with intertrochanteric fractures who underwent bipolar hemiarthroplasty have significantly higher 2- year mortality rate than similar patients underwent fixation with PFNA, while they did not experience higher length of stay than the PFNA group. Future prospective, multi center study with larger sample size will be likely to validate similar fixation choice needed to decrease the mortality rate in intertrochanteric fractures.